2016
DOI: 10.1186/s12912-016-0188-9
|View full text |Cite
|
Sign up to set email alerts
|

Nurses’ perceptions of a pressure ulcer prevention care bundle: a qualitative descriptive study

Abstract: BackgroundPressure ulcer prevention is a critical patient safety indicator for acute care hospitals. An innovative pressure ulcer prevention care bundle targeting patient participation in their care was recently tested in a cluster randomised trial in eight Australian hospitals. Understanding nurses’ perspectives of such an intervention is imperative when interpreting results and translating evidence into practice. As part of a process evaluation for the main trial, this study assessed nurses’ perceptions of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 31 publications
1
36
0
Order By: Relevance
“…The qualitative component of the study provided rich data about hospital staff's perceptions of the PUPP and identified what was working and what was missing. In particular, participants in the qualitative interviews identified two recommendations to strengthen the PUPP: (a) education programs targeting health care aides and (b) active patient participation (Chaboyer et al, , ; Gillespie, Chaboyer, Sykes, O'Brien, & Brandis, ; Latimer, Chaboyer, & Gillespie, ; Murray, ; Roberts et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The qualitative component of the study provided rich data about hospital staff's perceptions of the PUPP and identified what was working and what was missing. In particular, participants in the qualitative interviews identified two recommendations to strengthen the PUPP: (a) education programs targeting health care aides and (b) active patient participation (Chaboyer et al, , ; Gillespie, Chaboyer, Sykes, O'Brien, & Brandis, ; Latimer, Chaboyer, & Gillespie, ; Murray, ; Roberts et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Evidence‐based practice guidelines about PU prevention and treatment have been developed and promoted locally and globally (British Columbia Provincial Nursing Skin and Wound Committee, ; National Pressure Ulcer Advisory Panel, European Pressure Ulcer Advisory Panel, & Pan Pacific Pressure Injury Alliance, ; Registered Nurses' Association of Ontario, ; Winnipeg Regional Health Authority, ). Changing material resources and interventions may be challenging for some healthcare providers, but educational opportunities about evidence‐based practice have enhanced adoption of best practices (Baldelli & Paciella, ; Chaboyer et al, ; Chaboyer & Gillespie, ; Hunter, Kelly, Stanley, Stilley, & Anderson, ; Murray, ; Roberts et al, ; Schmidt & Brown, ).…”
Section: Introductionmentioning
confidence: 99%
“…37 The role of education tools is an important consideration in efforts to improve health literacy. Educating and involving patients in prevention and management of PIs has been identified as being important in clinical settings in Australia, 33,38,39 the United Kingdom, 40 the United States, 41,42 and other countries. 43,44 In Australia, the content and frequency of consumer education for sustained knowledge and best practices in prevention and management of PIs were included in a list of priority issues 45 with patients themselves expressing the need for ongoing education on PI prevention.…”
Section: Key Messagesmentioning
confidence: 99%
“…The role of education tools is an important consideration in efforts to improve health literacy. Educating and involving patients in prevention and management of PIs has been identified as being important in clinical settings in Australia, the United Kingdom, the United States, and other countries …”
Section: Introductionmentioning
confidence: 99%
“…Practice interviews with methodological experts (MW and AC) and renal clinicians (NAG) were undertaken. A semi‐structured interview guide was used to elicit information on local practices and staff attitudes to practice and to promote flexibility and responsiveness to the experiences and the roles of participants . Only data collected from the a priori domains of current processes around dialysis CVC use, insertion, maintenance and removal, were included in this substudy analysis.…”
Section: Methodsmentioning
confidence: 99%